(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters as follows:Introduction and research problem:Active learning is an educational philosophy that relies on the learner’s positivity in the educational situation and aims to activate the learner’s role in terms of learning through work, research and experimentation, and the learner’s self-reliance in obtaining information, acquiring skills, and forming values ​​and attitudes. problem solving and on teamwork, cooperative learning and peer learning.